A composite stabilizer for PVC and its preparation method and application
Through the modified composite stabilizer of titanium dioxide, organic acid salt intercalation zinc-aluminum lanthanum hydrotalcite and pentaerythritol ester, the problems of high cost and poor light stability of TiO2 particles are solved, and the photothermal stability and mechanical properties of PVC are improved. Achieve higher overall performance and compatibility.
Patent Information
- Application Number
- CN202410582850.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-05-11
- Publication Date
- 2024-12-31
- Estimated Expiration
- 2044-05-11
AI Technical Summary
In the prior art, TiO2 particles have high cost, poor light stability and poor compatibility with PVC substrates, resulting in insufficient comprehensive performance of PVC materials.
Complex stabilizers composed of modified titanium dioxide (TiO2/CQDs), organic acid intercalated zinc-aluminum lanthanum hydrotalcite (itaconate-ZnAlLa-LDHs) and tetrakis(3-mercaptopropionate)pentaerythritol ester (PETMP), through TiO2/CQDs were prepared by hydrothermal method, and the layer spacing of hydrotalcite was increased by itaconate-ZnAlLa-LDHs to form a synergistic effect to improve the photothermal stability and mechanical properties of PVC.
The photothermal stability, mechanical properties, flame retardancy and smoke suppression of PVC are significantly improved, the material cost is reduced, and the compatibility with PVC substrate is improved.
Smart Images

Figure CN118344651B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of polymer materials, and in particular to a composite stabilizer for PVC and a preparation method and application thereof. Background Art
[0002] Polyvinyl chloride (PVC) is one of the most widely used polymers in the world. It is made by polymerizing vinyl chloride monomer (VCM). PVC has a wide range of applications, including window frames, medical catheters and blood bags, curtains, wires, paints and packaging. However, PVC will undergo degradation reactions such as dehydrochlorination under ultraviolet light, causing PVC to age and shorten its service life. Therefore, sunscreens, UV absorbers and free radical scavengers are often used as light stabilizers in PVC products to delay light degradation.
[0003] Rutile titanium dioxide particles (TiO2) have a tetragonal structure and have a good shielding effect on ultraviolet light waves in the range of 290nm to 420nm. Due to its good ultraviolet absorption ability, high chemical and thermal stability, non-toxicity and environmental protection, it is used in PVC products as an ultraviolet absorber to slow down the yellowing and aging of PVC. Since TiO2 can only absorb ultraviolet rays, under ultraviolet irradiation, the photogenerated electrons and holes generated on the surface of TiO2 react with O2 adsorbed on the surface of TiO2 to generate O2 ·- , while the holes will oxidize the adsorbed H2O to generate ·OH, and the generated strong oxidizing free radicals will oxidize and degrade PVC. Therefore, when titanium dioxide is used as a UV absorber in PVC, it will cause photodegradation of PVC. In addition, since TiO2 nanoparticles have high surface activity, when directly added to PVC, agglomeration will occur, resulting in a decrease in the mechanical properties of the material. Therefore, how to improve the stability of TiO2 to PVC, reduce the cost of use, and improve the comprehensive performance of the product has become a hot topic in the industry.
[0004] At present, some studies have used self-made complexes to act together with TiO2 in PVC materials, which can reduce the amount of TiO2 particles to a certain extent while achieving the same stabilization effect; some scholars have compounded TiO2 particles with MgO particles and found that the addition of MgO can slow down the yellowing of the material; and when the ratio of TiO2 to MgO is 1:3, the comprehensive performance of the material after aging is improved.
[0005] However, the existing technology still lacks a composite stabilizer containing TiO2 for PVC to solve the problems of high cost, poor light stability and poor compatibility with PVC substrates of TiO2 particles in the existing technology, and to improve the comprehensive performance of PVC materials. Summary of the invention
[0006] The present invention provides a novel composite stabilizer for PVC and a preparation method and application thereof, which are proposed to address the deficiencies of the prior art, and improve the light and heat stability, mechanical properties, flame retardancy and smoke suppression of PVC products.
[0007] The first object of the present invention is to provide a composite stabilizer for PVC, characterized in that it comprises the following components by mass: 35-50% of modified titanium dioxide, 15-25% of organic acid salt intercalated zinc-aluminum-lanthanum hydrotalcite and 25%-40% of pentaerythritol tetrakis(3-mercaptopropionic acid);
[0008] Specifically, the modified titanium dioxide is TiO2 / CQDs, and the organic acid salt intercalated zinc aluminum lanthanum type hydrotalcite is itaconate-ZnAlLa-LDHs.
[0009] The second object of the present invention is to provide a method for preparing the above-mentioned composite stabilizer, the preparation method comprising:
[0010] S1 Preparation of TiO2 / CQDs
[0011] S11: uniformly dispersing a certain amount of TiO2 in deionized water by ultrasonication to obtain a TiO2 aqueous solution; adding a certain amount of maltitol to the TiO2 aqueous solution to obtain a solution a1;
[0012] S12: placing the mixed solution a1 in a hydrothermal synthesis reactor for heating treatment, and then washing with ethanol, separating and drying to obtain TiO2 / CQDs;
[0013] S2 Preparation of itaconate-ZnAlLa-LDHs:
[0014] S21: dissolving Al(NO3)3 and Zn(NO3)2 in a certain mass ratio in deionized water to obtain solution a2; then adding a certain amount of La(NO3)3 to solution a2 and stirring evenly to obtain solution a3;
[0015] S22: a certain amount of NaOH is dissolved in deionized water to obtain solution a4; a certain amount of itaconate is dissolved in ethanol to obtain solution a5;
[0016] S23: placing the solution a3 in a constant temperature water bath at 80° C., and sequentially adding the solution a4 and the solution a5 into the solution a3 to obtain a solution a6;
[0017] S24: subjecting solution a6 to a hydrothermal aging reaction, and finally subjecting it to a reduced pressure microporous filtration, washing, and drying in a constant temperature drying oven, and then grinding to obtain itaconate-ZnAlLa-LDHs;
[0018] S3 composite stabilizer for preparing PVC
[0019] 35-50% of TiO2 / CQDs, 15-25% of itaconate-ZnAlLa-LDHs and 25%-40% of pentaerythritol tetrakis(3-mercaptopropionate) are weighed separately, put into a mixing device, and uniformly mixed by mechanical stirring or ball milling to obtain a composite stabilizer for PVC.
[0020] Specifically, the mass ratio of TiO2 to maltitol in step S11 is 100:(2-5); the concentration of the TiO2 aqueous solution is 6-8 g / L.
[0021] Specifically, the mass ratio of Al(NO3)3, Zn(NO3)2 and La(NO3)3 in step S21 is (1.5-2):(4.5-5):(3.5-4); the concentration of Al(NO3) is 2.5-5 g / L.
[0022] Specifically, the concentration of NaOH in step S22 is 9-12 g / L; the mass ratio of NaOH to itaconate is 10:(3-5).
[0023] Specifically, the reaction time of the hydrothermal aging reaction in step S24 is 4 to 6 hours, and the reaction temperature is 110 to 140°C.
[0024] The third object of the present invention is to provide an application of the above-mentioned composite stabilizer for PVC in PVC products, wherein the PVC products include the following components by mass fraction: 90-95% PVC raw material, 0.05-0.3% composite stabilizer for PVC, 0.3-0.9% lubricant and 3-10% coating additive.
[0025] Specifically, the lubricant is PE100 wax, and the coating additive is Sec.
[0026] Specifically, the preparation method of the PVC product comprises: putting 90-95% of PVC raw materials, 0.05-0.3% of composite stabilizer for PVC, 0.3-0.9% of lubricant and 3-10% of coating additive into an internal mixer in sequence, mixing at 120°C for 10 minutes, and then putting the mixture into a double-roll plasticizer for tableting at a tableting temperature of 180°C for 3 minutes to obtain a PVC product.
[0027] Compared with the prior art, the beneficial effects of the present invention include:
[0028] (1) The present invention uses maltitol as a raw material and prepares TiO2 / CQDs by a hydrothermal method, so that carbon quantum dots (CQDs) are coated on the surface of TiO2, so that there are a large number of oxygen-containing functional groups on the surface of TiO2 / CQDs. The ketone oxygen and carboxyl ketone oxygen groups in CQDs can form hydrogen bonds with the polar groups of PVC to produce a fixation effect on HCl, thereby alleviating the thermal degradation of PVC caused by HCl, and further improving the light stability, long-term thermal stability and thermal degradation performance of PVC products; in addition, the abundant hydroxyl groups on CQDs can form a stable complex with the zinc atoms in ZnCl2, thereby avoiding the degradation of PVC catalyzed by free ZnCl2;
[0029] (2) The present invention uses itaconate as an intercalation agent and combines itaconate with zinc-aluminum-lanthanum hydrotalcite to prepare itaconate intercalated zinc-aluminum-lanthanum hydrotalcite (itaconate-ZnAlLa-LDHs), thereby increasing the interlayer distance of the hydrotalcite to provide a larger reaction space, exposing more active centers, and enhancing the absorption of HCl produced by the degradation of PVC, thereby preventing the breakage of the C-Cl bond and the C=C double bond in the PVC. In addition, the free radicals in the PVC will also react with itaconate-ZnAlLa-LDHs to produce ZnCl2, thereby inhibiting the occurrence of the "zinc burning" phenomenon and preventing the self-catalytic effect of PVC; at the same time, the dispersibility of itaconate-ZnAlLa-LDHs in the PVC matrix is improved; thereby, the interfacial adhesion strength between the components in the composite catalyst is improved, and the toughness and comprehensive tensile mechanical properties of the composite material are enhanced;
[0030] (3) The composite stabilizer of the present invention includes pentaerythritol tetrakis(3-mercaptopropionic acid)ester (PETMP), and PETMP is compounded with TiO2 / CQDs and itaconic acid-ZnAlLa-LDHs, so that the three play a synergistic role, further improving the thermal stability and comprehensive mechanical properties of PVC products; due to the formation of hydrogen bonds between the -SH group of PETMP and the -Cl polar group in PVC, a zinc alcohol complex can be formed between PETMP and itaconic acid-ZnAlLa-LDHs, which plays a role in stabilizing itaconic acid-ZnAlLa-LDHs in the PVC matrix; PETMP also strengthens the interaction between TiO2 / CQDs and the PVC matrix, forming a physical cross-linking structure in the PVC system, thereby improving the mechanical properties, flame retardancy and stability of PVC products;
[0031] (4) The composite stabilizer for PVC provided by the present invention, through compounding in a specific ratio, enables the three components to exert the maximum synergistic effect, and forms a stable system in the PVC matrix through physical crosslinking, wherein TiO2 / CQDs provides light stabilization and thermal stabilization effects, itaconate-ZnAlLa-LDHs enhances thermal stability and mechanical properties, and PETMP further improves the performance of PVC through crosslinking and enhanced interface effects. When applied to PVC products, the light stability, thermal stability, UV aging resistance, mechanical properties and flame retardancy of PVC can be greatly improved. BRIEF DESCRIPTION OF THE DRAWINGS
[0032] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0033] Figure 1 (A) is a TEM image of TiO2 prepared in Comparative Example 1 of the present invention;
[0034] Figure 1 (B) is a HRTEM image of TiO2 prepared in Comparative Example 1 of the present invention;
[0035] Figure 1 (C) TEM image of TiO2 / CQDs prepared in Example 1;
[0036] Figure 1 (D) is the HRTEM image of TiO2 / CQDs prepared in Comparative Example 1 of the present invention;
[0037] Figure 2 This is the XPS graph of TiO2 / CQDs prepared in Example 1 of the present invention;
[0038] Figure 3 (A) is a SEM image of CO3-ZnAlLa-LDHs prepared in Comparative Example 2 of the present invention;
[0039] Figure 3 (B) is a SEM image of itaconate-ZnAlLa-LDHs prepared in Example 1 of the present invention;
[0040] Figure 4 XRD comparison diagram of itaconate-ZnAlLa-LDHs prepared in Example 1 of the present invention and CO3-ZnAlLa-LDHs prepared in Comparative Example 2;
[0041] Figure 5A comparison chart of the effects of the composite stabilizers for PVC prepared in Examples 1-3 of the present invention and the stabilizers prepared in Comparative Examples 5-6 on the thermal stability of PVC products;
[0042] Figure 6 This is a comparison chart of the effects of the composite stabilizer for PVC prepared in Examples 1-2 of the present invention and the stabilizers prepared in Comparative Examples 3 and 5-6 on the light stability of PVC products. DETAILED DESCRIPTION
[0043] The following will combine the contents in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0044] Unless otherwise defined, all technical and scientific terms used in this specification have the same meaning as those commonly understood by those skilled in the art of the present invention. The terms used in the specification of the present invention are only for the purpose of describing specific embodiments and are not intended to limit the present invention. The term "and / or" used in this specification includes any and all combinations of one or more of the related listed items.
[0045] The experimental methods used in the following examples are conventional methods unless otherwise specified. The materials, reagents, etc. used in the following examples are all commercially available unless otherwise specified.
[0046] In the examples of the present invention, TiO2, maltitol, Zn(NO3)2 and itaconate were purchased from Aladdin Reagent Co., Ltd.; Al(NO3)3, NaOH, La(NO3)3 and NaHCO3 were purchased from Tianjin Kemeou Chemical Reagent Co., Ltd.; PETMP was purchased from New Pharmaceutical Chemical Reagent Co., Ltd.; and PVC resin was purchased from Sinopec Qilu Co., Ltd.
[0047] Example 1
[0048] S1 Preparation of TiO2 / CQDs
[0049] S11: 4 g of TiO2 is uniformly dispersed in 600 mL of deionized water by ultrasonication to obtain a TiO2 aqueous solution; 0.08 g of maltitol is added to the TiO2 aqueous solution to obtain a solution a1;
[0050] S12: The mixed solution a1 is placed in a hydrothermal synthesis reactor and heated at 180°C for 12 hours, then washed with ethanol and centrifuged three times, and dried in a vacuum oven at 70°C for 6 hours to obtain TiO2 / CQDs prepared in Example 1.
[0051] S2 Preparation of itaconate-ZnAlLa-LDHs
[0052] S21: Dissolve 5 g of Al(NO3)3 and 11.25 g of Zn(NO3)2 in 1000 mL of deionized water to obtain solution a2; then add 8.75 g of La(NO3)3 to solution a2 and stir to obtain solution a3;
[0053] S22: 12.5 g of NaOH was dissolved in 1000 mL of deionized water to obtain solution a4; 3.75 g of itaconate was dissolved in 1000 mL of ethanol to obtain solution a5;
[0054] S23: placing the solution a3 in a constant temperature water bath at 80° C., and sequentially adding solution a4 and solution a5 into solution a3 to obtain solution a6;
[0055] S24: Solution a6 is subjected to hydrothermal aging reaction at 110°C for 4 hours, and finally filtered and washed under reduced pressure. After drying in a constant temperature drying oven, it is ground to obtain itaconate-ZnAlLa-LDHs prepared in Example 1.
[0056] S3 composite stabilizer for preparing PVC
[0057] 9 g of TiO2 / CQDs prepared in Example 1, 4.5 g of itaconate-ZnAlLa-LDHs prepared in Example 1 and 7.5 g of PETMP were weighed respectively, put into a mixing device, and mechanically stirred for 30 min to mix evenly to obtain a composite stabilizer for PVC, which was recorded as B1.
[0058] Preparation of PVC products
[0059] The composite stabilizer B1 for PVC prepared in Example 1 was applied to PVC products. The following raw materials were calculated by mass, including the following components: 63g of PVC, 0.2g of composite stabilizer for PVC, 0.84g of B1PE100 wax and 0.2g of sike. The above raw materials were put into an internal mixer in turn and mixed at 120°C for 10 minutes, and then put into a double-roll plasticizer for tableting. The tableting temperature was 180°C and the roller diameter was 110cm. After the roller temperature was kept constant, continuous mixing was started to obtain the PVC product prepared in Example 1, which was recorded as PVC+B1.
[0060] Example 2
[0061] S1 Preparation of TiO2 / CQDs
[0062] S11: 4.8 g of TiO2 is uniformly dispersed in 600 mL of deionized water by ultrasonication to obtain a TiO2 aqueous solution; 0.2 g of maltitol is added to the TiO2 aqueous solution to obtain a solution a1;
[0063] S12: The mixed solution a1 is placed in a hydrothermal synthesis reactor and heated at 180°C for 12 hours, then washed with ethanol and centrifuged three times, and dried in a vacuum oven at 70°C for 6 hours to obtain TiO2 / CQDs prepared in Example 2.
[0064] S2 Preparation of itaconate-ZnAlLa-LDHs
[0065] S21 Take 8g of Al(NO3)3 and 20g of Zn(NO3)2 and dissolve them in 500mL of deionized water to obtain solution a2; then add 16g of La(NO3)3 to solution a2 and stir to obtain solution a3;
[0066] S22: 13.5 g of NaOH was dissolved in 1000 mL of deionized water to obtain solution a4; 6.5 g of itaconate was dissolved in 1000 mL of ethanol to obtain solution a5;
[0067] S23: placing the solution a3 in a constant temperature water bath at 80° C., and sequentially adding the solution a4 and the solution a5 into the solution a3 to obtain a solution a6;
[0068] S24: Solution a6 is subjected to hydrothermal aging reaction at 140°C for 6 hours, and finally filtered and washed under reduced pressure. After drying in a constant temperature drying oven, it is ground to obtain itaconate-ZnAlLa-LDHs prepared in Example 2.
[0069] S3 composite stabilizer for preparing PVC
[0070] Weigh 5 g of TiO2 / CQDs prepared in Example 2, 2.5 g of itaconate-ZnAlLa-LDHs prepared in Example 2 and 4 g of PETMP respectively, put them into a mixing device, and mix them evenly by mechanical stirring for 30 minutes to obtain a composite stabilizer for PVC, which is recorded as B2.
[0071] Preparation of PVC products
[0072] The composite stabilizer B2 for PVC prepared in Example 2 was applied to PVC products. The following raw materials were calculated by mass, including the following components: 65g of PVC, 0.1g of composite stabilizer for PVC, 0.5g of B1PE100 wax and 0.3g of Sec, which were put into an internal mixer in sequence and mixed at 120°C for 10min, and then put into a double-roll plasticizer for tableting. The tableting temperature was 180°C and the roller diameter was 110cm. After the roller temperature was kept constant, continuous mixing was started to obtain the PVC product prepared in Example 2, which was recorded as PVC+B2.
[0073] Example 3
[0074] S1 Preparation of TiO2 / CQDs
[0075] S11: 4.2 g of TiO2 is uniformly dispersed in 600 mL of deionized water by ultrasonication to obtain a TiO2 aqueous solution; 0.09 g of maltitol is added to the TiO2 aqueous solution to obtain a solution a1;
[0076] S12: The mixed solution a1 is placed in a hydrothermal synthesis reactor and heated at 180°C for 12 hours, then washed with ethanol and centrifuged three times, and dried in a vacuum oven at 70°C for 6 hours to obtain TiO2 / CQDs prepared in Example 3.
[0077] S2 Preparation of itaconate-ZnAlLa-LDHs
[0078] S21: Dissolve 5 g of Al(NO3)3 and 13.9 g of Zn(NO3)2 in 1000 mL of deionized water to obtain solution a2; then add 10.8 g of La(NO3)3 to solution a2 and stir to obtain solution a3;
[0079] S22: 10.8 g of NaOH was dissolved in 1000 mL of deionized water to obtain solution a4; 4.4 g of itaconate was dissolved in 1000 mL of ethanol to obtain solution a5;
[0080] S23: placing the solution a3 in a constant temperature water bath at 80° C., and sequentially adding solution a4 and solution a5 into solution a3 to obtain solution a6;
[0081] S24: Solution a6 is subjected to hydrothermal aging reaction at 120°C for 5 hours, and finally filtered and washed under reduced pressure. After drying in a constant temperature drying oven, it is ground to obtain itaconate-ZnAlLa-LDHs prepared in Example 3.
[0082] S3 composite stabilizer for preparing PVC
[0083] 4 g of TiO2 / CQDs prepared in Example 3, 1.8 g of itaconate-ZnAlLa-LDHs prepared in Example 3 and 3 g of PETMP were weighed respectively, put into a mixing device, and mechanically stirred for 30 min to mix evenly to obtain the composite stabilizer for PVC prepared in Example 3, which was recorded as B3.
[0084] Preparation of PVC products
[0085] The composite stabilizer B3 for PVC prepared in Example 3 was applied to PVC products. The following raw materials were calculated by mass, including the following components: 60g of PVC, 0.3g of composite stabilizer for PVC, 0.4g of B1PE100 wax and 0.15g of Sec, which were put into an internal mixer in sequence and mixed at 120°C for 10min, and then put into a double-roll plasticizer for tableting. The tableting temperature was 180°C and the roller diameter was 110cm. After the roller temperature was kept constant, continuous mixing was started to obtain the PVC product prepared in Example 3, which was recorded as PVC+B3.
[0086] Example 4
[0087] S1 Preparation of TiO2 / CQDs
[0088] S11: 4.6 g of TiO2 is uniformly dispersed in 600 mL of deionized water by ultrasonication to obtain a TiO2 aqueous solution; 0.18 g of maltitol is added to the TiO2 aqueous solution to obtain a solution a1;
[0089] S12: The mixed solution a1 is placed in a hydrothermal synthesis reactor and heated at 180°C for 12 hours, then washed with ethanol and centrifuged three times, and dried in a vacuum oven at 70°C for 6 hours to obtain TiO2 / CQDs prepared in Example 4.
[0090] S2 Preparation of itaconate-ZnAlLa-LDHs
[0091] S21: Dissolve 4.3 g of Al(NO3)3 and .2 g of Zn(NO3)2 in 1000 mL of deionized water to obtain solution a2; then add 8 g of La(NO3)3 to solution a2 and stir to obtain solution a3;
[0092] S22: 12.7 g of NaOH was dissolved in 1000 mL of deionized water to obtain solution a4; 5.1 g of itaconate was dissolved in 1000 mL of ethanol to obtain solution a5;
[0093] S23: placing the solution a3 in a constant temperature water bath at 80° C., and sequentially adding solution a4 and solution a5 into solution a3 to obtain solution a6;
[0094] S24: Solution a6 is subjected to hydrothermal aging reaction at 110°C for 4 hours, and finally filtered and washed under reduced pressure. After drying in a constant temperature drying oven, it is ground to obtain itaconate-ZnAlLa-LDHs prepared in Example 4.
[0095] S3 composite stabilizer for preparing PVC
[0096] 15 g of TiO2 / CQDs prepared in Example 4, 6 g of itaconate-ZnAlLa-LDHs prepared in Example 4 and 12 g of PETMP were weighed respectively, put into a mixing device, and mechanically stirred for 30 min to mix evenly to obtain a composite stabilizer for PVC, which was recorded as B4.
[0097] Preparation of PVC products
[0098] The composite stabilizer B4 for PVC prepared in Example 4 was applied to PVC products. The following raw materials were calculated by mass, including the following components: 62g of PVC, 0.15g of composite stabilizer for PVC, 0.9g of B1PE100 wax and 0.2g of Sec, which were put into an internal mixer in sequence and mixed at 120°C for 10min, and then put into a double-roll plasticizer for tableting. The tableting temperature was 180°C and the roller diameter was 110cm. After the roller temperature was kept constant, continuous mixing was started to obtain the PVC product prepared in Example 4, which was recorded as PVC+B4.
[0099] Comparative Example 1
[0100] The difference between Comparative Example 1 and Example 1 is that TiO2 is not modified, and the other aspects are the same.
[0101] S3 composite stabilizer for preparing PVC
[0102] 9 g of TiO2, 4.5 g of itaconate-ZnAlLa-LDHs prepared in Comparative Example 1 and 7.5 g of PETMP were weighed respectively, put into a mixing device, and mechanically stirred for 30 minutes to mix evenly to obtain a composite stabilizer for PVC, which was recorded as D1.
[0103] Preparation of PVC products
[0104] The composite stabilizer D1 for PVC prepared in Comparative Example 1 was applied to PVC products. The following raw materials were calculated by mass, including the following components: 63g of PVC, 0.2g of composite stabilizer D1 for PVC, 0.84g of B1PE100 wax and 0.2g of Sec, which were successively put into an internal mixer and mixed at 120°C for 10min, and then put into a double-roll plasticizer for tableting. The tableting temperature was 180°C and the roller diameter was 110cm. After the roller temperature was kept constant, continuous mixing was started to obtain the PVC product prepared in Comparative Example 1, which was recorded as PVC+D1.
[0105] Comparative Example 2
[0106] The difference between Comparative Example 2 and Example 1 is that the aluminum-lanthanum ternary hydrotalcite is the traditional CO3-ZnAlLa-LDHs, and the other parts are the same.
[0107] Preparation of CO3-ZnAlLa-LDHs by S2
[0108] S21: Dissolve 5 g of Al(NO3)3 and 11.25 g of Zn(NO3)2 in 1000 mL of deionized water to obtain solution a2; then add 8.75 g of La(NO3)3 to solution a2 and stir to obtain solution a3;
[0109] S22: 8.5 g of NaOH and 4.2 g of NaHCO3 are dissolved in 1000 mL of deionized water to obtain solution a4;
[0110] S23: placing the solution a3 in a constant temperature water bath at 80° C., and sequentially adding the solution a4 into the solution a3 to obtain a solution a6;
[0111] S24: Solution a6 was subjected to hydrothermal aging reaction at 110°C for 4 hours, and finally filtered and washed under reduced pressure. After drying in a constant temperature drying oven, the CO3-ZnAlLa-LDHs prepared in Comparative Example 2 was obtained by grinding.
[0112] S3 composite stabilizer for preparing PVC
[0113] 9 g of TiO2 / CQDs prepared in Example 1, 4.5 g of CO3-ZnAlLa-LDHs prepared in Comparative Example 2 and 7.5 g of PETMP were weighed respectively, put into a mixing device, and mechanically stirred for 30 min to mix evenly to obtain a composite stabilizer for PVC, which was recorded as D2.
[0114] Preparation of PVC products
[0115] The composite stabilizer D2 for PVC prepared in Comparative Example 2 was applied to PVC products. The following raw materials were calculated by mass, including the following components: 63g of PVC, 0.2g of composite stabilizer D2 for PVC, 0.84g of B1PE100 wax and 0.2g of Sec, which were successively put into an internal mixer and mixed at 120°C for 10 minutes, and then put into a double-roll plasticizer for tableting. The tableting temperature was 180°C and the roller diameter was 110cm. After the roller temperature was kept constant, continuous mixing was started to obtain the PVC product prepared in Comparative Example 2, recorded as PVC+D2.
[0116] Comparative Example 3
[0117] The difference between Comparative Example 3 and Example 1 is that the composite catalyst for PVC finally prepared does not contain PETMP, and the other aspects are the same.
[0118] S3 composite stabilizer for preparing PVC
[0119] 9 g of TiO2 / CQDs prepared in Example 1 and 4.5 g of itaconate-ZnAlLa-LDHs prepared in Example 1 were weighed respectively and put into a mixing device. The mixture was mechanically stirred for 30 min and mixed evenly to obtain a composite stabilizer for PVC, which was recorded as D3.
[0120] Preparation of PVC products
[0121] The composite stabilizer D3 for PVC prepared in Comparative Example 3 was applied to PVC products. The following raw materials were calculated by mass, including the following components: 63g of PVC, 0.2g of composite stabilizer D3 for PVC, 0.84g of B1PE100 wax and 0.2g of Sec, which were put into an internal mixer in sequence and mixed at 120°C for 10min, and then put into a double-roll plasticizer for tableting. The tableting temperature was 180°C and the roller diameter was 110cm. After the roller temperature was kept constant, continuous mixing was started to obtain the PVC product prepared in Comparative Example 3, recorded as PVC+D3.
[0122] Comparative Example 4
[0123] The difference between Comparative Example 4 and Example 1 is that the final prepared composite catalyst for PVC does not contain TiO2 / CQDs, and the other aspects are the same.
[0124] S3 composite stabilizer for preparing PVC
[0125] 4.5 g of itaconate-ZnAlLa-LDHs prepared in Example 1 and 7.5 g of PETMP were weighed and put into a mixing device, and mechanically stirred for 30 minutes to mix them evenly to obtain a composite stabilizer for PVC, which was recorded as D3.
[0126] Preparation of PVC products
[0127] The composite stabilizer D3 for PVC prepared in Comparative Example 3 was applied to PVC products. The following raw materials were calculated by mass, including the following components: 63g of PVC, 0.2g of composite stabilizer D4 for PVC, 0.84g of B1PE100 wax and 0.2g of Sec, which were successively put into an internal mixer and mixed at 120°C for 10 minutes, and then put into a double-roll plasticizer for tableting. The tableting temperature was 180°C and the roller diameter was 110cm. After the roller temperature was kept constant, continuous mixing was started to obtain the PVC product prepared in Comparative Example 4, recorded as PVC+D4.
[0128] Comparative Example 5
[0129] The difference between Comparative Example 5 and Example 1 is that the composite catalyst for PVC finally prepared does not contain itaconate-ZnAlLa-LDHs, and the other parts are the same.
[0130] S3 composite stabilizer for preparing PVC
[0131] 9 g of TiO2 / CQDs prepared in Example 1 and 7.5 g of PETMP were weighed separately, put into a mixing device, and mechanically stirred for 30 min to mix them evenly to obtain a composite stabilizer for PVC, which was recorded as D5.
[0132] Preparation of PVC products
[0133] The composite stabilizer D5 for PVC prepared in Comparative Example 5 was applied to PVC products. The following raw materials were calculated by mass, including the following components: 63g of PVC, 0.2g of composite stabilizer D5 for PVC, 0.84g of B1PE100 wax and 0.2g of Sec, which were successively put into an internal mixer and mixed at 120°C for 10 minutes, and then put into a double-roll plasticizer for tableting. The tableting temperature was 180°C and the roller diameter was 110cm. After the roller temperature was kept constant, continuous mixing was started to obtain the PVC product prepared in Comparative Example 5, which was recorded as PVC+D5.
[0134] Comparative Example 6
[0135] In Comparative Example 6, no stabilizer was added when preparing the PVC product.
[0136] Preparation of PVC products
[0137] The following raw materials are calculated by weight, including the following components: 63g of PVC, 0.84g of B1PE100 wax and 0.2g of succinic acid. The above raw materials are mixed in a WNH-200 high-speed pulverizer according to the weight of the raw materials, and the stirring speed is 50r / min. The PVC product prepared in Comparative Example 6 is obtained, which is recorded as PVC.
[0138] Performance Testing
[0139] Structural characterization
[0140] X-ray diffraction (XRD) spectra were measured by a Brucker D8 Advance diffractometer (Cu Kα radiation, λ=1.54 nm) with a beam voltage of 40 kV and a current of 44 mA. Transmission electron microscopy (TEM) and high-resolution transmission electron microscopy (HRTEM, Tecnai G2F20) were used to observe the microstructure of the material. Using 300 W aluminum Kα X-rays as the excitation source, the X-ray photoelectron spectrum (XPS, Kratos Axis UltraDLD spectrometer) of the material was measured; Fourier transform infrared spectroscopy (FTIR) was obtained by a Nicolet 5700 spectrometer in the United States, with a test range of 400-4000 cm -1 .
[0141] See also Figure 1 , Figure 1 (A) is a TEM image of TiO2 prepared in Comparative Example 1 of the present invention; Figure 1 (B) is a HRTEM image of TiO2 prepared in Comparative Example 1 of the present invention; Figure 1 (C) TEM image of TiO2 / CQDs prepared in Example 1; Figure 1 (D) is the HRTEM image of TiO2 / CQDs prepared in Comparative Example 1 of the present invention; Figure 1 (A)-1(D) shows that TiO2 has a spherical structure, while Figure 1 (C) shows that there are lattice fringes in the TiO2 / CQDs structure, and the crystal plane spacing is 0.36nm, which matches the in-plane lattice of rutile nano-titanium dioxide. It can be seen that after its surface is modified by CQDs, the particle size and morphology of TiO2 / CQDs have no obvious changes; Figure 1 In (D), it can be seen that the lattice fringes with a spacing of 0.18 nm belong to CQDs, which proves that CQDs have a modification effect on the TiO2 surface.
[0142] Please refer to Figure 2 , Figure 2 XPS graph of TiO2 / CQDs prepared in Example 1 of the present invention; Figure 2 The full XPS spectrum shows the presence of C, O, and Ti elements in TiO2 / CQDs, indicating that the TiO2 surface has been wrapped and modified by CQDs.
[0143] Please refer to Figure 3 , Figure 3 (A) is a SEM image of CO3-ZnAlLa-LDHs prepared in Comparative Example 2 of the present invention; Figure 3 (B) is the SEM image of itaconate-ZnAlLa-LDHs prepared in Example 1 of the present invention; Figure 3As can be seen from (A), CO3-ZnAlLa-LDHs is a regular hexagon with a layered structure of uniform size; Figure 3 (B) It can be seen that after inserting itaconate, the shape of itaconate-ZnAlLa-LDHs changes to an irregular hexagon, which does not affect its hydrotalcite-like flake structure, but the size is significantly reduced, the flake thickness decreases from 50nm to 16nm, the flake size decreases from 526nm to 159nm, and the scale of the material changes from subnanometer to nanometer. It can be seen that after adding itaconate, the hydrotalcite is evenly distributed, which is significantly improved compared with the agglomeration phenomenon of CO3-ZnAlLa-LDHs.
[0144] Please refer to Figure 4 , Figure 4 XRD comparison diagram of itaconate-ZnAlLa-LDHs prepared in Example 1 of the present invention and CO3-ZnAlLa-LDHs prepared in Comparative Example 2; Figure 4 It can be seen that the diffraction peak of itaconicate-ZnAlLa-LDHs is sharp, the baseline is smooth, and it has a layered structure and better regularity. Compared with CO3-ZnAlLa-LDHs, the diffraction peak of itaconicate-ZnAlLa-LDHs on the (003) crystal plane has a small angle shift from 2θ=11.54° to 2θ=9.91°, and the interlayer spacing increases from 0.763nm to 0.902nm (2dsinθ=nλ). This is due to the larger volume of itaconicate, indicating that itaconicate has entered the interlayer of aluminum-lanthanum ternary hydrotalcite and obtained a better intercalation product.
[0145] Thermal stability test
[0146] The thermal stability of PVC products was tested using thermogravimetric analysis (TGA) using the STA449 (NETZSCH) thermogravimetric analyzer thermogravimetric analyzer: heating rate 20℃ / min, nitrogen flow rate 50mL / min, temperature detection range 50-600℃, test the change of weight loss of PVC products with temperature.
[0147] Please refer to Figure 5 , Figure 5 This is a comparison chart of the effects of the composite stabilizers for PVC prepared in Examples 1-3 of the present invention and the stabilizers prepared in Comparative Examples 5-6 on the thermal stability of PVC products; Figure 5It can be seen that all PVC products obviously experience two rapid weight loss stages during the heating process. In the range of 250-350℃, the first stage of weight loss can be attributed to the degradation of the PVC main chain, releasing HCl and small hydrocarbons and forming conjugated polyene structures; (2) in the range of 350-470℃, it is characterized by the formation of aromatic compounds due to the cyclization of polyenes; (3) above 470℃, it is characterized by the decomposition of aromatic compounds. The first stage is the most important stage because the main function of the heat stabilizer is to fix HCl, effectively delaying the release of HCl, thereby inhibiting its autocatalytic effect on PVC and effectively improving the thermal stability of PVC. From Figure 5 It can be seen that when the composite stabilizer for PVC prepared in Examples 1-3 is added to the PVC product, the initial degradation temperature of the first stage is improved compared with that of Comparative Examples 5-6, and the weight loss rate is also lower than that of Comparative Examples 5-6. Therefore, it can be seen that the composite catalyst for PVC prepared by the present invention can effectively inhibit the thermal degradation of PVC products, and its thermal stability is improved.
[0148] Photostability test
[0149] Spread the PVC product (PVC+B1) in Example 1 on a smooth glass plate. Move it to a 120℃ oven for plasticization for 20 minutes, and cut it into 1×1cm small square pieces after cooling. Place the PVC small square pieces under ultraviolet light, take samples every 1 hour for the first time, and then take samples every 6 hours each time to observe the color change of the PVC product. Please refer to the test results Figure 6 , Figure 6The following is a comparison chart of the effects of the composite stabilizer for PVC prepared in Examples 1-2 of the present invention and the stabilizer prepared in Comparative Examples 3, 5-6 on the light stability of PVC products. The initial color of the pure PVC without stabilizer in Comparative Example 6 is slightly yellow, which turns brown after 6 hours and dark after 12 hours. In the PVC prepared in Comparative Example 5, the addition of TiO2 / CQDs and PETMP greatly improves the whiteness of the PVC, but serious heat aging still occurs. After 18 hours of heat treatment, the PVC turns dark brown. In the PVC prepared in Comparative Example 2, the addition of TiO2 / CQDs and itaconicate-ZnAlLa-LDHs improves the heat aging of the PVC, but at 24 hours, light aging still occurs, which may be because TiO2 / CQDs and itaconicate-ZnAlLa-LDHs are unevenly dispersed in the PVC matrix and may overflow, resulting in a failure to play a significant role in improving light stability. The composite stabilizer prepared in Examples 1-2 of the present invention includes TiO2 / CQDs, itaconicate-ZnAlLa-LDHs and PETMP. With this specific component as a stabilizer, the light aging rate of PVC is significantly slowed down, and it does not turn dark brown even after 60 hours of illumination, which proves the improvement effect of the composite catalyst prepared in Examples 1-2 of the present invention on the ultraviolet light stability of PVC.
[0150] Mechanical properties test
[0151] According to GB / T 1040.3.2006, the tensile properties were measured on the American MTS E43 equipment at 500 mm / min, and the average value of five samples was calculated and recorded;
[0152] Mechanical properties test: The PVC sheet products obtained in Examples 1-4 and Comparative Examples 1-6 were tested according to the plastic tensile properties test method of GB / T1040-1992. The specific steps of the test method are: the obtained PVC sheets in Examples 1-4 and Comparative Examples 1-5 were made into standard dumbbell II-type specimens, and then the specimens were placed on a KDIII-5 microcomputer-controlled electronic universal testing machine for testing, with a tensile speed of 50 mm / min, and the tensile strength and elongation at break were tested, and the average values of five samples were calculated and the test results were recorded. The test results are shown in Table 1:
[0153] Table 1
[0154] Example / Comparative Example name Tensile strength / MPa Elongation at break / % Example 1 PVC+B1 23.7 565.6 Example 2 PVC+B2 22.8 545.7 Example 3 PVC+B3 23.4 558.2 Example 4 PVC+B4 23.6 539.5 Comparative Example 1 PVC+D1 22.9 518.4 Comparative Example 2 PVC+D2 20.4 458.3 Comparative Example 3 PVC+D3 21.7 476.2 Comparative Example 4 PVC+D4 21.2 465.9 Comparative Example 5 PVC+D5 20.3 450.8 Comparative Example 6 PVC 18.6 423.6
[0155] From the data in Table 1, it can be seen that the tensile strength and elongation at break of Comparative Example 6, i.e., PVC without stabilizer, are the worst, which indicates that during the thermal processing, the thermal stability of Comparative Example 1 is the worst, resulting in a certain degree of thermal aging of the PVC and a significant decrease in the mechanical properties; the tensile strength and elongation at break of Comparative Example 1 and Comparative Examples 3-4 are slightly lower than those of Examples 1-4, which indicates that TiO2 / CQDs and itaconate-ZnAlLa-LDHs both contribute to thermal stability to a certain extent; the tensile strength and elongation at break of Comparative Examples 2 and 5 are significantly lower than those of Examples 1-4, which indicates that itaconate-ZnAlLa-LDHs significantly improves the mechanical properties of PVC. Moreover, the PVC prepared by the composite stabilizer in Examples 1-4 has a tensile strength of 21.5% higher than that of pure PVC, which is 18.6. Therefore, the composite stabilizer composed of TiO2 / CQDs, itaconicate-ZnAlLa-LDHs and PETMP containing a specific ratio forms a stable system in the PVC matrix through the synergistic effect of the three. TiO2 / CQDs and itaconicate-ZnAlLa-LDHs mainly enhance the mechanical properties of PVC, while PETMP further improves the mechanical properties of PVC through cross-linking and enhanced interface effects, has an enhancing effect on plasticized PVC, and the elongation at break is also increased by more than 25%.
[0156] Flame retardant and smoke suppression test
[0157] The PVC products prepared in Examples 1-2 and Comparative Examples 3-6 were measured by a cone calorimeter (CONE) at 50 kW·m -2 Parameters such as carbon residue rate, heat release rate, total heat release rate, smoke production rate and total smoke production rate under different conditions.
[0158] Total smoke release TSP (m 2 / m 2 ): is the smoke generation rate SPR (m 2 / s) versus time (s). Total smoke production rate SPR (m 2 / s): product of specific extinction area SEA and mass loss rate MLR: SPR (m 2 / s)=SEA(m 2 / Kg)×MLR(g -1 )×0.001.
[0159] The test results are shown in Table 2:
[0160] Table 2
[0161]
[0162] Compared with pure PVC, the carbon residue rate of the PVC products containing the composite stabilizer prepared in Examples 1-2 is significantly increased, while the total smoke production rate is significantly reduced, indicating that the PVC is converted into carbon residue without being completely burned under the composite stabilizer, thereby avoiding the generation of a large amount of toxic smoke. In addition, the PVC products containing the composite stabilizer release less heat during the combustion process. This shows that the PVC products prepared in Examples 1-2 have flame retardancy and smoke suppression.
[0163] The present invention uses a specific combination of PETMP, TiO2 / CQDs and itaconic acid-ZnAlLa-LDHs as a composite stabilizer for PVC. In the process of preparing PVC products, free radicals on the PVC macromolecular chain will generate chemical bonds and a small amount of physical adsorption with itaconic acid-ZnAlLa-LDHs, thereby enhancing the dispersibility of itaconic acid-ZnAlLa-LDHs in the PVC matrix and improving the interface adhesion strength between the two phases. In TiO2 / CQDs, pure TiO2 itself has good ultraviolet absorption capabilities and the ability to generate electrons and holes, but the generated holes have strong oxidizing properties and will cause PVC to be oxidatively degraded. However, when CQDs are loaded on the surface of TiO2, CQDs can convert ultraviolet light into fluorescence to prevent the generation of holes. In addition, ketone oxygen and carboxyl ketone oxygen groups in CQDs fix HCl by forming hydrogen bonds with polar groups in PVC, and hydroxyl groups in CQDs can also form coordination bonds to bind ZnCl2, thereby avoiding free ZnCl2 from catalyzing the degradation of PVC, thereby improving the thermal stability of PVC. The addition of PETMP enables the three components to exert the maximum synergistic effect, forming a stable system in the PVC matrix and forming a physical cross-linking structure; PETMP and itaconate-ZnAlLa-LDHs can form a zinc alcohol complex, which stabilizes itaconate-ZnAlLa-LDHs in the PVC matrix; in addition, through the hydrogen bond formed between the -SH group of PETMP and the polar group of PVC, the interaction with the PVC matrix is strengthened. The composite stabilizer obtained by compounding it is applied to PVC products to form a physical cross-linking structure in the PVC system, which can greatly improve the light and heat stability, UV aging resistance, flame retardancy and mechanical properties of PVC.
[0164] Meanwhile, the contents not described in detail in this specification belong to the prior art known to those skilled in the art.
[0165] It should be noted that, in this article, relational terms such as first and second, etc. are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Moreover, the terms "include", "comprise" or any other variants thereof are intended to cover non-exclusive inclusion, so that a process, method, article or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or device.
[0166] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.
Claims
1. A composite stabilizer for PVC, characterized in that: The invention comprises the following components in mass fraction: 35-50% of modified titanium dioxide, 15-25% of organic acid salt intercalated zinc aluminum lanthanum type hydrotalcite and 25-40% of pentaerythritol tetrakis (3-mercaptopropionic acid); wherein the modified titanium dioxide is TiO2 / CQDs, the organic acid salt intercalated zinc aluminum lanthanum type hydrotalcite is itaconate-ZnAlLa-LDHs; and the itaconate is itaconate; The preparation method of the composite stabilizer for PVC comprises: S1 Preparation of TiO2 / CQDs S11: uniformly dispersing a certain amount of TiO2 in deionized water by ultrasonication to obtain a TiO2 aqueous solution; adding a certain amount of maltitol to the TiO2 aqueous solution to obtain a solution a1; the mass ratio of the TiO2 to the maltitol is 100:(2-5); S12: placing the mixed solution a1 in a hydrothermal synthesis reactor for heating treatment, and then washing with ethanol, separating and drying to obtain TiO2 / CQDs; S2 Preparation of itaconate-ZnAlLa-LDHs: S21: dissolving Al(NO3)3 and Zn(NO3)2 in a certain mass ratio in deionized water to obtain solution a2; then adding a certain amount of La(NO3)3 to solution a2, stirring evenly to obtain solution a3; the mass ratio of Al(NO3)3, Zn(NO3)2 and La(NO3)3 is (1.5~2):(4.5~5):(3.5~4); S22: a certain amount of NaOH is dissolved in deionized water to obtain solution a4; a certain amount of itaconate is dissolved in ethanol to obtain solution a5; the mass ratio of NaOH to itaconate is 10:(3-5); S23: placing the solution a3 in a constant temperature water bath at 80° C., and sequentially adding the solution a4 and the solution a5 into the solution a3 to obtain a solution a6; S24: subjecting solution a6 to a hydrothermal aging reaction, and finally subjecting it to a reduced pressure microporous filtration, washing, and drying in a constant temperature drying oven, and then grinding to obtain itaconate-ZnAlLa-LDHs; S3 composite stabilizer for preparing PVC 35-50% of TiO2 / CQDs, 15-25% of itaconate-ZnAlLa-LDHs and 25-40% of pentaerythritol tetrakis(3-mercaptopropionate) were weighed respectively, put into a mixing device, and uniformly mixed by mechanical stirring or ball milling to obtain a composite stabilizer for PVC.
2. A method for preparing the composite stabilizer according to claim 1, characterized in that: The preparation method comprises: S1 Preparation of TiO2 / CQDs S11: uniformly dispersing a certain amount of TiO2 in deionized water by ultrasonication to obtain a TiO2 aqueous solution; adding a certain amount of maltitol to the TiO2 aqueous solution to obtain a solution a1; the mass ratio of the TiO2 to the maltitol is 100:(2-5); S12: placing the mixed solution a1 in a hydrothermal synthesis reactor for heating treatment, and then washing with ethanol, separating and drying to obtain TiO2 / CQDs; S2 Preparation of itaconate-ZnAlLa-LDHs: S21: dissolving Al(NO3)3 and Zn(NO3)2 in a certain mass ratio in deionized water to obtain solution a2; then adding a certain amount of La(NO3)3 to solution a2, stirring evenly to obtain solution a3; the mass ratio of Al(NO3)3, Zn(NO3)2 and La(NO3)3 is (1.5~2):(4.5~5):(3.5~4); S22: a certain amount of NaOH is dissolved in deionized water to obtain solution a4; a certain amount of itaconate is dissolved in ethanol to obtain solution a5; the mass ratio of NaOH to itaconate is 10:(3-5); S23: placing the solution a3 in a constant temperature water bath at 80° C., and sequentially adding the solution a4 and the solution a5 into the solution a3 to obtain a solution a6; S24: subjecting solution a6 to a hydrothermal aging reaction, and finally subjecting it to a reduced pressure microporous filtration, washing, and drying in a constant temperature drying oven, and then grinding to obtain itaconate-ZnAlLa-LDHs; S3 composite stabilizer for preparing PVC 35-50% of TiO2 / CQDs, 15-25% of itaconate-ZnAlLa-LDHs and 25-40% of pentaerythritol tetrakis(3-mercaptopropionate) were weighed respectively, put into a mixing device, and uniformly mixed by mechanical stirring or ball milling to obtain a composite stabilizer for PVC.
3. The preparation method according to claim 2, characterized in that: The concentration of the TiO2 aqueous solution in step S11 is 6-8 g / L.
4. The preparation method according to claim 2, characterized in that: The concentration of Al(NO3)3 in step S21 is 2.5~5g / L.
5. The preparation method according to claim 2, characterized in that: The concentration of NaOH in step S22 is 9-12 g / L.
6. The preparation method according to claim 2, characterized in that: The reaction time of the hydrothermal aging reaction in step S24 is 4-6 hours, and the reaction temperature is 110-140°C.
7. Use of the composite stabilizer for PVC as claimed in claim 1 in PVC products, characterized in that: The PVC product is composed of the following components in mass fractions: 90-95% of PVC raw material, 0.05-0.3% of composite stabilizer for PVC, 0.3-0.9% of lubricant and 3-10% of coating additive.
8. The use according to claim 7, characterized in that: The lubricant is PE100 wax, and the coating additive is Sec.
9. The use according to claim 7, characterized in that: The preparation method of the PVC product comprises: putting 90-95% of PVC raw material, 0.05-0.3% of composite stabilizer for PVC, 0.3-0.9% of lubricant and 3-10% of coating additive into an internal mixer in sequence, mixing at 120° C. for 10 minutes, and then putting the raw material into a double-roll plasticizer for tableting at a tableting temperature of 180° C. for 3 minutes to obtain the PVC product.